Quality of Life Among High-Risk Antenatal Women in a Tertiary Care Hospital Kerala, South India - Chittilappilly Jose, Princy; Nayak, Sabitha; Kattukaran, Anoj; Reghunath, Rajee; Veigas, Jacintha (Indonesian Socety of Obstetrics and Gynecology, 2025)
Objectives: The study aims to assess the quality of life (QoL) among high-risk antenatal women and to determine its association with selected baseline and obstetric variables. Methods: A cross-sectional design was utilized, and 82 high-risk antenatal women meeting the inclusion criteria were purposively sampled from the antenatal outpatient department of a tertiary care hospital in Kerala, South India. Data collection involved a structured questionnaire to evaluate baseline, obstetric factors, and the QOL/GRAV Questionnaire to measure QoL. Data were analysed using SPSS version 23. Categorical variables were summarized as frequencies and percentages. The association between selected variables and quality of life (QoL) was assessed using Fisher’s Exact test, and regression analysis was performed to identify predictors of low QoL. Results: The mean QoL scores of the respondents in the current study were 30.43 ± 4.461, which suggests a good QoL despite potential pregnancy-related challenges. The presence of leg cramps, anaemia, and multiple pregnancies among high-risk antenatal women was significantly associated with reduced QoL. Conclusion: The findings provide insights into the QoL in high-risk antenatal populations, emphasizing the need for tailored interventions to improve maternal health outcomes. Key words:antenatal women,high risk, quality of life